2006
DOI: 10.1021/ic0609610
|View full text |Cite
|
Sign up to set email alerts
|

Metal Binding to Bipyridine-Modified PNA

Abstract: Substitution of natural nucleobases in PNA oligomers with ligands is a strategy for directing metal ion incorporation to specific locations within a PNA duplex. In this study, we have synthesized PNA oligomers that contain up to three adjacent bipyridine ligands and examined the interaction with Ni2+ and Cu2+ of these oligomers and of duplexes formed from them. Variable-temperature UV spectroscopy showed that duplexes containing one terminal pair of bipyridine ligands are more stable upon metal binding than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 33 publications
4
81
1
Order By: Relevance
“…147 However, the incorporation of multiple M 2+ -bipy moieties in the centre of a PNA duplex did not grant greater thermal stability, probably because of electrostatic and steric interactions between adjacent, positively charged complexes. 147 Moreover, UV titrations showed that the presence of several bipy ligands in close proximity to each other in PNA oligomers exerts a chelate effect, which favours the formation of complexes in which the metal ion coordinates the maximum number of accessible ligands. 147 It is noteworthy that the melting temperatures did not change in the presence of 148 In the case of 11-containing PNA oligomers, Achim et al showed by variable-temperature UV-vis spectroscopy that, in the presence of Cu 2+ , duplexes were formed even from 11-containing strands that have a large number of mismatches.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 98%
See 4 more Smart Citations
“…147 However, the incorporation of multiple M 2+ -bipy moieties in the centre of a PNA duplex did not grant greater thermal stability, probably because of electrostatic and steric interactions between adjacent, positively charged complexes. 147 Moreover, UV titrations showed that the presence of several bipy ligands in close proximity to each other in PNA oligomers exerts a chelate effect, which favours the formation of complexes in which the metal ion coordinates the maximum number of accessible ligands. 147 It is noteworthy that the melting temperatures did not change in the presence of 148 In the case of 11-containing PNA oligomers, Achim et al showed by variable-temperature UV-vis spectroscopy that, in the presence of Cu 2+ , duplexes were formed even from 11-containing strands that have a large number of mismatches.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 98%
“…147 With this in mind, Achim and co-workers have inserted up to three consecutive 8-hydroxyquinoline-(11, Figure 14) or bipyridine (bipy)-modified (12, Figure 14) PNA monomers into PNA oligomers. [147][148][149][150] They then examined in detail the interaction of these oligomers with different metal ions and also the stability of duplexes formed from them. In the case of 12, variable-temperature UV spectroscopy showed that duplexes containing one terminal pair of bipyridine ligands are more stable upon metal binding with Ni 2+ and Cu 2+ than their non-modified counterparts.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 99%
See 3 more Smart Citations